Validating the crèche educator emotional style questionnaire among Chinese kindergarten teachers - Chang, Biru; Guo, Qiuxia; Wu, Xingxing (Frontiers in Psychology, 2025)
IntroductionKindergarten teachers are important emotional socialization agents for preschoolers’ social–emotional competence, and their meta-emotion philosophy might either enhance or inhibit preschoolers’ emotional socialization. Due to the lack of relative measurements, no studies have paid much attention to Chinese kindergarten teachers’ meta-emotion philosophy.MethodsThe present study included multistage research to evaluate the psychometric properties of the Crèche Educator Emotional Style Questionnaire (CEESQ) among Chinese kindergarten teachers. In Study One, exploratory factor analyses (EFAs) were conducted to assess the factor structure among 535 Chinese preschool teachers. In Study Two, confirmatory factor analyses (CFAs) were performed to confirm the factor structures among 538 other Chinese preschool teachers. The measurement invariance and convergent validity of the Chinese versions of CEESQ were also assessed. The results indicated that the five-factor model was a feasible representation of the Chinese version of CEESQ factor structure (χ2/df = 3.70, CFI = 0.93, TLI = 0.92, RMSEA [90% CI] = 0.061 [0.057, 0.065], RMSEA = 0.05). A multigroup CFA indicated the measurement invariance considering teachers’ parenting experiences, amount of teaching experiences, and academic education level.ResultsThe Chinese version of CEESQ had robust internal consistency reliability and concurrent validity with emotional intelligence. The Chinese version of CEESQ had sound psychometric characteristics to evaluate Chinese kindergarten teachers’ meta-emotion philosophy.ConclusionThis study added to the existing research literature by supporting the applicability of CEESQ among Chinese kindergarten teachers.